A SPX domain‐containing phosphate transporter from Rhizophagus irregularis handles phosphate homeostasis at symbiotic interface of arbuscular mycorrhizas. Issue 2 (21st February 2022) - Xie, Xianan; Lai, Wenzhen; Che, Xianrong; Wang, Sijia; Ren, Ying; Hu, Wentao; Chen, Hui; Tang, Ming
Summary: Reciprocal symbiosis of > 70% of terrestrial vascular plants with arbuscular mycorrhizal (AM) fungi provides the fungi with fatty acids and sugars. In return, AM fungi facilitate plant phosphate (Pi) uptake from soil. However, how AM fungi handle Pi transport and homeostasis at the symbiotic interface of AM symbiosis is poorly understood. Here, we identify an SPX (SYG1/Pho81/XPR1) domain‐containing phosphate transporter, RiPT7 from Rhizophagus irregularis . To characterize the RiPT7 transporter, we combined subcellular localization and heterologous expression studies in yeasts with reverse genetics approaches during the in planta phase. The results show that RiPT7 is conserved across fungal species and expressed in the intraradical mycelia. It is expressed in the arbuscules, intraradical hyphae and vesicles, independently of Pi availability. The plasma membrane‐localized RiPT7 facilitates bidirectional Pi transport, depending on Pi gradient across the plasma membrane, whereas the SPX domain of RiPT7 inhibits Pi transport activity and mediates the vacuolar targeting of RiPT7 in yeast in response to Pi starvation. Importantly, RiPT7 silencing hampers arbuscule development of R. irregularis and symbiotic Pi delivery under medium‐ to low‐Pi conditions. Collectively, our findings reveal a role for RiPT7 in fine‐tuning of Pi homeostasis across the fungal membrane to maintain the AM development.